Urgensi Maqashid Syariah dalam Pengelolaan Harta - Syahputra, Angga; Asmuni, Asmuni; Anggraini, Tuti (Jurnal Iqtisaduna, 2023)
Lots of life problems experienced by humans due to lack of wealth, but on the other hand, people who have excess wealth also experience many problems. Generally, people who have excess wealth will be arrogant and arbitrary, feel that everything can be managed and see other people who are below them in a small way. A study has found a clear link between wealth and indifference to the feelings of others. In Indonesia, we receive a lot of information through various media about the arrogant attitudes of rich people. Increasingly, news about this matter has become routine consumption for the community and of course it will have an adverse impact. For this reason, researchers want to further examine how the urgency of maqasid sharia is in managing assets. This research is a descriptive qualitative research. To answer the existing problems, researchers will use secondary data that has been previously published. This research concludes that humans must be aware of the nature of their existence and the various resources they have are not absolute ownership, because absolute ownership belongs only to Allah Swt. The big step to free oneself from mismanagement of wealth and greed is to return to God, Allah Swt. and focuses on how to be a better Muslim